Strategi Pengembangan Sektor Pariwisata Pantai Mantau dalam Meningkatkan Kesejahteraan Masyarakat Ditinjau dalam Perspektif Ekonomi Syariah: Studi Kasus Pariwisatan Pantai Mantau di Desa Nanga Wera Kec. Wera Kab. Bima - Jumiati; Rafiuddin; Dinah Husniah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
At Mantau Beach there are many problems due to the lack of attention from the local government causing Mantau Beach to not be a promising tourist attraction for the region. So this research aims to find out the views of the local community about the application of sharia economic principles in developing tourism on mantau beach and the development strategy of the mantau beach tourism sector can improve the welfare of the nanga wera village community with sharia economic principles. This research will be conducted in Nanga Village, Wera District, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques are Observation and Interview. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study that the local community has a very positive view of the application of sharia economic principles in the development of the Mantau Beach tourism sector and the Mantau Beach tourism sector development strategy in Nanga Wera Village based on sharia economic principles is an approach that is not only oriented towards economic growth, but also emphasizes the importance of justice, blessings, and Islamic values in every economic activity.